48. CELIAC PLEXUS BLOCK COMBINED WITH ERECTOR SPINAE PLANE BLOCK FOR ANALGESIA AFTER PANCREATICODUODENECTOMY: A FIVE-CASE REPORT (Vietnam Journal of Community Medicine, 2025)
Background: Open pancreaticoduodenectomy (Whipple procedure) is associated with significant postoperative pain. Although epidural analgesia is effective, it carries safety concerns and a notable failure rate. The celiac plexus block combined with the erector spinae plane block can provide coverage for both visceral and somatic pain, potentially offering several advantages.Case presentation: We report 5 scheduled Whipple procedure cases (ASA II-III) in which patients received intraoperative celiac plexus block with 20 ml of 0.2% Ropivacaine and bilateral continuous erector spinae plane block with 0.1% Ropivacaine infusion. Assessment parameters included VAS pain scores, Morphine consumption, hemodynamic events, time to first flatus, and block-related complications during the first 72 hours postoperatively.Results: Mean resting VAS was 2.1 ± 0.5 at all time points, remaining below 4 in all patients; mean dynamic VAS was 2.7 ± 0.6. The mean Morphine requirement was 1.2 mg over 72 hours. No hemodynamic instability (bradycardia or hypotension) or technique-related complications were observed.Conclusions: The combination of intraoperative celiac plexus block and continuous bilateral erector spinae plane block provided effective and safe analgesia in all five cases. Further studies are warranted to confirm these preliminary findings.
Keywords: Celiac plexus block, erector spinae plane block, postoperative analgesia, Whipple procedure, multimodal analgesia, Bach Mai Hospital.